2020
DOI: 10.1002/viw.20200046
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic iron oxide nanomaterials: A key player in cancer nanomedicine

Abstract: Magnetic iron oxide nanomaterials are among the most widely studied candidates for cancer nanomedicine, because of not only their great biocompatibility and abundance of raw materials, but also their diverse physicochemical properties and biological effects. Represented by magnetite and maghemite, various iron oxide‐based magnetic nanomaterials have been developed for cancer diagnosis and treatment. This mini review presents an up‐to‐date overview of magnetic iron oxide‐based cancer nanomedicines with an empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 82 publications
(98 reference statements)
0
19
0
Order By: Relevance
“…However, to date, only iron oxide nanoparticles have been approved for the magnetic response diagnosis and the magnetic hyperthermia tumor therapy (Park et al, 2017 ; Shi et al, 2017 ). Few clinical trials have been reported for any tumor therapy based on ferrite nanoparticle-induced ROS (Liang et al, 2020 ). The ferrite nanoparticle-induced ROS can kill the cancer cell and also can trigger the toxic effect on the normal tissues and vasculature.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…However, to date, only iron oxide nanoparticles have been approved for the magnetic response diagnosis and the magnetic hyperthermia tumor therapy (Park et al, 2017 ; Shi et al, 2017 ). Few clinical trials have been reported for any tumor therapy based on ferrite nanoparticle-induced ROS (Liang et al, 2020 ). The ferrite nanoparticle-induced ROS can kill the cancer cell and also can trigger the toxic effect on the normal tissues and vasculature.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…[ 148 ] Fe 3 O 4 was found with property of peroxidase‐mimicking in 2007, [ 149 ] leading to its broad range of biomedical applications. [ 150–152 ] The successful development of Fe 3 O 4 also triggers the developing transition metal‐based nanozymes and noble metal based nanozymes as well as their biomedical applications, such as Co, [ 153 ] Zr, [ 154 ] V, [ 155 ] Pt, [ 156 ] and Au. [ 157 ] Notably, the well‐designed carbon nanomaterials are considered as ideal candidates for nanozyme and have exhibited with enhanced biocatalytic performance as peroxidase mimics, superoxide dismutase (SOD) mimics and hydrolase mimics.…”
Section: The Application Of Sustainable Carbon Materials In Catalysismentioning
confidence: 99%
“…Nanomedicine can be characterized into three broad categories: regenerative medicine, nano-diagnosis and nano-therapy (Figure 5). Regenerative medicine utilizes nanomaterials such as carbon nanostructures, diamond polymers, polymeric nanoparticles and silica nanoparticles to replace or repair damaged tissues or organs through surface modeling [84,87]. In nano-diagnostics, nanoparticles are used both in vitro and in vivo as imaging sensors to detect abnormal cells or diseases that can be detected outside of the host in biological fluids [85].…”
Section: The Age Of Nanomedicinementioning
confidence: 99%